Pre- and post-injury job type distributions of individuals with SCI in relation to structural changes in the labor market: A comparative analysis based on findings from the Swiss Spinal Cord Injury Cohort Study - Schwegler, Urban (J Spinal Cord Med, 2019)
Objective: To compare pre- and post-injury job type distributions of individuals with spinal cord injury (SCI) living in Switzerland. Design: Cross-sectional, self-report survey. Setting: Community. Participants: Two hundred sixty-three individuals reporting a pre- and 677 a post-injury job title in the Swiss SCI Cohort Study community survey. Interventions: Not applicable. Outcome Measures: Job titles were elicited by free-text questions and classified using the International Standard Classification of Occupations (ISCO-08). Frequencies across ISCO-08 major groups were calculated and compared to Swiss labor market statistics for 1995 and 2011. Results: Compared to pre-SCI, Professionals (16.3% vs 31.2%) and Clerical Support Workers (11.7% vs 19.1%) were more prevalent and Crafts and Related Workers (26.5% vs 5.4%) less common post-injury. Except for Clerical Support Workers, these results reflect recent structural changes in the Swiss labor market. Conclusion: The higher post-SCI prevalence of jobs predominantly requiring cognitive and communication skills compared to rather physically oriented jobs mirrors structural changes in the labor market, except for clerical jobs. Future return-to-work strategies should not primarily target the clerical sector with its diminishing job opportunities, but promote vocational re-training towards jobs requiring higher education and assistive technology to return individuals with limited cognitive resources to physically oriented jobs.